Treatment patterns and outcomes in patients with advanced melanoma in France. (October 2013) - Bedane, Christophe; Leccia, Marie-Thérèse; Sassolas, Bruno; Bregman, Bruno; Lebbé, Céleste
Abstract Background: Melanoma is associated with high mortality and poor response to standard chemotherapy. In order to benchmark benefits of recently introduced treatments, outcome with standard chemotherapy in everyday practice should be documented. Objectives: To document treatment pathways in patients with advanced melanoma, to compare clinical outcomes between treatment lines, and to measure associated healthcare resource utilisation in terms of hospital visits and adverse event management. Methods: An observational, longitudinal survey of patients with unresectable stage III/IV melanoma in France evaluated 278 patients with ≥2 months follow-up. Data were collected retrospectively for 2–3 years following the index consultation. Treatment history was documented and outcomes determined for each treatment line. Complete and partial response rates were compared between treatment lines. Overall and progression-free survival were determined by Kaplan–Meier analysis. Health resource utilisation was documented hospitalisations, hospice stays, emergency room visits, outpatient visits and adverse event management. Results: In total, 271 patients (97.5%) received first-line therapy, 161 (57.9%) second-line therapy and 85 (30.6%) third-line therapy. The most frequent first-line therapy strategies were systemic treatment alone (46.5%) or in combination with surgery (22.9%). The most frequently used chemotherapy was dacarbazine monotherapy (62.3% of chemotherapy). Median duration of first-line systemic therapy was 11.9 (IQR: 6.6–24.0) weeks. First-line therapy was discontinued in 190 patients (68.3%), principally due to disease progression (150 patients). Median overall survival was 17.1 (95% CI: 14.6–20.1) months since diagnosis, 9.5 (95% CI: 6.7–12.8) months since initiation of first-line therapy and 5.3 (95% CI: 3.7–7.2) months since initiation of second-line therapy. Median progression-free survival time was 2.8 (95% CI: 2.5–3.3) months. Ninety-six patients (40.2%) received medication to manage adverse events and 131 patients (47.1%) required hospitalisation (mean: 3.1 hospitalisations; mean duration: 27 days). Study limitations: The retrospective data collection precludes ascertainment of medical information and completion of missing data. Conclusions: Existing therapies provide limited survival benefit to patients with unresectable stage III/IV melanoma. New more effective treatment options are needed.